2019
DOI: 10.1002/pits.22322
|View full text |Cite
|
Sign up to set email alerts
|

Teacher–student relationship quality and math achievement: The mediating role of teacher self‐efficacy

Abstract: The relation between social dyadic variables such as teacher–student relationship quality (TSRQ) and student achievement have been well‐documented within prior work; however, less research has focused on how TSRQ associates with achievement. We used longitudinal structural equation modeling to investigate the extent that teacher self‐efficacy mediated the relationship between TSRQ and math achievement for 881 children in the National Institute of Child Health and Human Development Study. Teacher–student closen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 79 publications
(137 reference statements)
5
29
0
2
Order By: Relevance
“…This instrument is operationally similar to the STRS-SF, with 7 items measuring anticipated closeness with future students and 8 items measuring anticipated conflict with future students. Descriptive statistics for the closeness and conflict subscales of the ATSRQ are comparable to recently published results using the STRS-SF with ISTs (e.g., Hajovsky et al, 2020a;Hajovsky et al, 2020b;Hajovsky et al, 2021;Mason et al, 2017). One observable difference between PST and IST samples is that PSTs anticipated slightly more conflict with their future students than ISTs experienced with their current students.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This instrument is operationally similar to the STRS-SF, with 7 items measuring anticipated closeness with future students and 8 items measuring anticipated conflict with future students. Descriptive statistics for the closeness and conflict subscales of the ATSRQ are comparable to recently published results using the STRS-SF with ISTs (e.g., Hajovsky et al, 2020a;Hajovsky et al, 2020b;Hajovsky et al, 2021;Mason et al, 2017). One observable difference between PST and IST samples is that PSTs anticipated slightly more conflict with their future students than ISTs experienced with their current students.…”
Section: Discussionsupporting
confidence: 77%
“…Dissimilar to conflict, the longitudinal trajectory of teachers' ratings of closeness with a student demonstrates an exponential decline during primary school (e.g., Hajovsky et al, 2020a;Jerome et al, 2009). Even with the decline, teachers with strong self-efficacy beliefs consistently rate their relationships with students as being closer than those with low self-efficacy beliefs over time (e.g., Hajovsky et al, 2020a;Hajovsky et al, 2020b).…”
Section: Conceptualization and Measurement Of Teacher-student Relationship Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of these findings, in some longitudinal studies, it was concluded that teacher self-efficacy increased significantly from the beginning of teacher education to the first year in profession, but there was no significant difference in attitudes towards the profession and at the end of four years prospective teachers' attitudes towards teaching profession did not change (Tanel & Tanel, 2013;Bümen & Özaydın, 2013). Teachers with high instructional self-efficacy devote more time to academic learning in the classroom, support students who need help to succeed, and have an impact on students' success (Freeman, 2008;Hajovsky et al 2020;Woolfolk & Hoy, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Framed in Bandura's social cognitive theory, teacher self-efficacy is defined as "the teacher's belief in his or her capability to organize and execute courses of action required to successfully accomplish a specific teaching task in a particular context" (Tschannen-Moran et al, 1998, p. 233). Teachers with high levels of self-efficacy beliefs are distinguished by having a greater commitment to the teaching profession and its students (Chesnut and Burley, 2015); showing greater openness to change and innovation (Bandura, 1997;Tsigilis et al, 2007); spending more time teaching in class (Organization for Economic Co-operation and Development [OECD], 2019a); having a more positive affect (Burić and Moè, 2020); presenting greater levels of instructional quality (Künsting et al, 2016;Burić and Kim, 2020); tending to collaborate to a greater extent with other teachers (Skaalvik and Skaalvik, 2010); and establishing closer relationships with their students (Zee and Koomen, 2017;Hajovsky et al, 2020;Wettstein et al, 2021).…”
Section: Teachers' Self-efficacy: Its Meaning and Measurementmentioning
confidence: 99%